Atom electronics in single-molecule transistors: single-atom access and manipulation. Issue 1 (31st December 2023) - Ouyang, Yiping; Wang, Feng; Zhang, Minhao; Qin, Yuyuan; Tan, Yuan-Zhi; Ji, Wei; Song, Fengqi
ABSTRACT: The aim of atom electronics, i.e. the final scale of electronics, is to make use of specific individual atoms as active electronic components. Here, we review recent researches on atom electronics in single-molecule transistors (SMTs) through single-atom access and manipulation. We begin by describing the basic concepts and characteristics of atom electronics in SMTs, before discussing some of the most recent examples, including atomic transistors and atomic storage. In our concluding remarks, we discuss some perspectives on fabrication, integration, and other potential atomic devices in which high precision access to, and manipulation of single atoms could be of great significance. This will affect integrated circuits, quantum computing, and other devices that will drive the electronics of the future. Graphical abstract: uf0001